Peran Guru Dalam Mengembangkan Kemampuan Bahasa Ekspresif Pada Anak Kelompok B - Pontoh, Vriska; Arifin, Irvin Novita; Laiya, Sri Wahyuningsi (Early Childhood Education Department, Faculty of Education, State University of Gorontalo, 2024)
The objective of this research was to describe the role of the teacher in developing expressive language skills in children of group B at TK (Kindergarten) Damhil DWP, Universitas Negeri Gorontalo City. This research employed a qualitative approach, with descriptive metdhos and data collection techniques used were observation, interviews, and documentation. The research subjects were teachers and children in Class B of TK Damhil. Meanwhile, the data analysis was carried out by describing things found in the field related to the role of the teacher as an educator, teacher as a teacher, and teacher as a guide for children in developing their language. The findings depicted that, in the process of developing expressive language in children at school, the teacher provided learning facilities and media to develop language in children, supervised children’s learning activities, and always provided motivation/encouragement to children during the learning process.